Delayed hypersensitivity reaction to hyaluronic acid dermal filler following influenza-like illness - Turkmani MG; De Boulle K; Philipp-Dormston WG (Dove Medical Press, 2019)
Mohammed G Turkmani,1 Koenraad De Boulle,2 Wolfgang G Philipp-Dormston31Derma Clinic, Riyadh, Saudi Arabia; 2Aalst Dermatology Clinic, Aalst, Belgium; 3Cologne Dermatology, Cologne, GermanyBackground: Delayed reactions after facial hyaluronic acid injection are relatively rare complications. Their cause may be infectious or immune-mediated in origin, and their outbreak can be triggered, for example, by an influenza-like illness.Objective: To describe potential adverse event of influenza like illness following dermal filler injection.Methods: We report fourteen unusual cases of delayed hypersensitivity reaction to several brands of hyaluronic acid dermal filler following influenza like illness.Results: Increasing evidence implicates influenza infection in the pathogenesis of late onset filler reaction.Conclusion: Although there is a low risk of late onset adverse reaction with hyaluronic acid fillers, injecting physicians must be aware of the possible filler reaction following the influenza infection.Keywords: fillers, hyaluronic acid, reaction, hypersensitivity, complications, influenza, infection